Removal Of Colour And Organic Pollutants From Textile Wastewater Using Integrated Biological And Advanced Oxidation Process - Mohamed Ahmed, Adel (2007)

(untitled)
Textile industrial wastewater effluent varies greatly in characteristics within a plant and even from the same process from time to time. Removal of pollutants such as colour and organics by conventional techniques has been difficult and could not reach the level of required discharge. In this study, colour and organic removals from textile wastewater in a continuous process using an integrated system of activated sludge and advanced oxidation process was studied. The primary objective was to reduce colour to 50 PtCo; the total organic carbon (TOC), chemical oxygen demand (COD), biochemical oxygen demand (BOD), and total suspended solid (TSS) to less than 20, 50, 20 and 20 mg/l, respectively; and to remove oil and grease (O&G). Activated sludge was satisfactory in terms of removing TOC, COD, BOD, O&G and TSS. At 36 h retention time, the removal of TOC, COD, BOD, O&G and TSS were 80, 78, 79, 53 and 61%, respectively. However, the colour removal was only 37%. With equalization tank, combining of 50 mg/l O3 with 1 ml/l H2O2 and UV was proven capable of reducing the colour, TOC, COD, BOD, O&G and TSS after 60 min by 97, 60, 64, 62, 90 and 36%, respectively. Without equalization tank, activated sludge treatment was efficient in terms of removing TOC, COD, BOD, O&G and TSS from the different strengths of textile wastewater samples. Removals of TOC, COD, BOD, O&G and TSS were 76-86, 77-84, 78-82, 34-61 and 65-74%, respectively. However, colour removal was from 17 to 34%. This means that activated sludge was satisfactory in removing only organics pollutants. Having different, easy control and successful processes that treat different strengths of textile wastewater is the best formulation of process treatment options to ensure appreciable removals of colour and organic pollutants from any strength of textile wastewater. A software called TexTreat was successfully developed. It can determine the required process treatment option of AOPs for any existing textile treatment plant and predict the characteristics of the final discharge using different retention times. The validation of the process treatment options using TexTreat shows their applicability with different textile wastewater plants.